2017
DOI: 10.1021/acs.jafc.7b02918
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary n-6:n-3 PUFA Ratios on Lipid Levels and Fatty Acid Profile of Cherry Valley Ducks at 15–42 Days of Age

Abstract: The objective of this study was to investigate the effects of dietary n-6:n-3 PUFA ratio on growth performance, serum and tissue lipid levels, fatty acid profile, and hepatic expression of fatty acid synthesis genes in ducks. A total of 3168 15-day old ducks were fed different n-6:n-3 PUFA ratios: 13:1 (control), 10:1, 8:1, 6:1, 4:1, and 2:1. The feeding trial lasted 4 weeks. Our results revealed that dietary n-6:n-3 PUFA ratios had no effects on growth performance. The 2:1 group had the highest serum triglyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 47 publications
9
15
0
Order By: Relevance
“…The deposition of fatty acids in meat was a complex and dynamic process, that could be affected by various factors such as age, sex, breed and rearing conditions of the animals. In the current study, we identified 20 fatty acids in duck breast muscle and found that the species and predominance order of indicated fatty acids were similar to previous reports [14,27,28]. We compared the composition of fatty acid between male and female ducks and found that it was really difficult to make a clear conclusion about the influence of duck sex on fatty acid composition of breast muscle.…”
Section: Effect Of Age Sex and Breeds On The Accumulation Of Fatty Asupporting
confidence: 79%
“…The deposition of fatty acids in meat was a complex and dynamic process, that could be affected by various factors such as age, sex, breed and rearing conditions of the animals. In the current study, we identified 20 fatty acids in duck breast muscle and found that the species and predominance order of indicated fatty acids were similar to previous reports [14,27,28]. We compared the composition of fatty acid between male and female ducks and found that it was really difficult to make a clear conclusion about the influence of duck sex on fatty acid composition of breast muscle.…”
Section: Effect Of Age Sex and Breeds On The Accumulation Of Fatty Asupporting
confidence: 79%
“…Fatty acid profiles of LDM and SAT samples were determined by gas chromatography as previously reported [15]. Briefly, samples were extracted with a mixture of chloroform and methanol (2:1; v/v) according to the methods previously described [16].…”
Section: Fatty Acid Composition Analysismentioning
confidence: 99%
“…In aquatic animals, health status is generally considered to be closely related to their antioxidant stress capacity. It has been reported that the substitution of FM with BSFM in fish diets could enhance the antioxidant properties by increasing the activities of certain antioxidant enzymes (T-SOD and GSH-Px) along with T-AOC (Li et al, 2017;[23, 39-41]). In this study, hepatic GSH-Px and T-SOD activities together with T-AOC significantly augmented in the 10%, 15%, and 20% BSFM diet groups.…”
Section: Discussionmentioning
confidence: 99%
“…All indicators were measured under the manufacturer's protocols. 2017) [23]. The moisture content of the samples was determined by high-temperature drying (105 °C) for 2 h. The crude protein was quantified by Kjeldahl method after acid treatment.…”
Section: Measurements Of Hepatic Antioxidant and Oxidationmentioning
confidence: 99%